Exploration of Post-traumatic Stress Disorder (PTSD) and Resilience in Female Internally Trafficked Domestic Workers from Nepal - Mounton, Patrice; Myers, Billie Clare; Gurung, Babita; Nagarkoti, Rojina (Apex Journal of Business and Management, 2024)
In the midst of adversity, such as trauma, individuals may possess resilience to effectively cope. The current investigation explored resilience and post-traumatic stress disorder (PTSD) in female domestic service workers who experienced internal trafficking in Nepal. The purpose of the qualitative components of the research was to code for resilience and symptoms of PTSD; whereas, the purpose of the quantitative component was to compare a group of female participants who experienced former or current domestic service work to a group of female participants who did not experience former or current domestic service work. The current study was a mixed methods approach in which 25 participants completed a resilience and PTSD questionnaire, and 13 of those participants who were also former or current domestic service workers participated in semistructured interviews about their experiences as domestic service workers. The results revealed high levels of PTSD among those who experienced domestic service work, but not higher or lower levels of resilience than those who did not experience domestic service work. Instead, qualitative research showed the presence of resilience in spite of having symptoms of PTSD among those who experienced domestic service work. These findings partially supported the hypothesis and suggest the need to further study those with high levels of resilience who also were internally trafficked, domestic service workers to understand how these individuals survive in spite of complex trauma.